Cody

Solution 1980125

Submitted on 17 Oct 2019 at 12:27 by Nikolaos Nikolaou
This solution is locked. To view this solution, you need to provide a solution of the same size or smaller.

Test Suite

Test Status Code Input and Output
1   Pass
A = [1 2; -3 0]; y_correct = -3; assert(isequal(sumOfN(A),y_correct))

y = 1 0 -3 0 y = 0 0 -3 0 y = 0 0 -3 0 y = -3

2   Pass
A = ones(8); y_correct = 0; assert(isequal(sumOfN(A),y_correct))

y = 1 0 0 0 0 0 0 0 1 1 0 0 0 0 0 0 1 1 1 0 0 0 0 0 1 1 1 1 0 0 0 0 1 1 1 1 1 0 0 0 1 1 1 1 1 1 0 0 1 1 1 1 1 1 1 0 1 1 1 1 1 1 1 1 y = 0 0 0 0 0 0 0 0 1 1 0 0 0 0 0 0 1 1 1 0 0 0 0 0 1 1 1 1 0 0 0 0 1 1 1 1 1 0 0 0 1 1 1 1 1 1 0 0 1 1 1 1 1 1 1 0 1 1 1 1 1 1 1 1 y = 0 0 0 0 0 0 0 0 1 0 0 0 0 0 0 0 1 1 1 0 0 0 0 0 1 1 1 1 0 0 0 0 1 1 1 1 1 0 0 0 1 1 1 1 1 1 0 0 1 1 1 1 1 1 1 0 1 1 1 1 1 1 1 1 y = 0 0 0 0 0 0 0 0 1 0 0 0 0 0 0 0 1 1 0 0 0 0 0 0 1 1 1 1 0 0 0 0 1 1 1 1 1 0 0 0 1 1 1 1 1 1 0 0 1 1 1 1 1 1 1 0 1 1 1 1 1 1 1 1 y = 0 0 0 0 0 0 0 0 1 0 0 0 0 0 0 0 1 1 0 0 0 0 0 0 1 1 1 0 0 0 0 0 1 1 1 1 1 0 0 0 1 1 1 1 1 1 0 0 1 1 1 1 1 1 1 0 1 1 1 1 1 1 1 1 y = 0 0 0 0 0 0 0 0 1 0 0 0 0 0 0 0 1 1 0 0 0 0 0 0 1 1 1 0 0 0 0 0 1 1 1 1 0 0 0 0 1 1 1 1 1 1 0 0 1 1 1 1 1 1 1 0 1 1 1 1 1 1 1 1 y = 0 0 0 0 0 0 0 0 1 0 0 0 0 0 0 0 1 1 0 0 0 0 0 0 1 1 1 0 0 0 0 0 1 1 1 1 0 0 0 0 1 1 1 1 1 0 0 0 1 1 1 1 1 1 1 0 1 1 1 1 1 1 1 1 y = 0 0 0 0 0 0 0 0 1 0 0 0 0 0 0 0 1 1 0 0 0 0 0 0 1 1 1 0 0 0 0 0 1 1 1 1 0 0 0 0 1 1 1 1 1 0 0 0 1 1 1 1 1 1 0 0 1 1 1 1 1 1 1 1 y = 0 0 0 0 0 0 0 0 1 0 0 0 0 0 0 0 1 1 0 0 0 0 0 0 1 1 1 0 0 0 0 0 1 1 1 1 0 0 0 0 1 1 1 1 1 0 0 0 1 1 1 1 1 1 0 0 1 1 1 1 1 1 1 0 y = 0

3   Pass
A = [-1 -3 -6; -6 0 -5; 1 2 5] y_correct = -6; assert(isequal(sumOfN(A),y_correct))

A = -1 -3 -6 -6 0 -5 1 2 5 y = -1 0 0 -6 0 0 1 2 5 y = 0 0 0 -6 0 0 1 2 5 y = 0 0 0 -6 0 0 1 2 5 y = 0 0 0 -6 0 0 1 2 0 y = -6

4   Pass
A = [-1 -3 -6; -6 0 -5; 1 2 -1] y_correct = -6; assert(isequal(sumOfN(A),y_correct))

A = -1 -3 -6 -6 0 -5 1 2 -1 y = -1 0 0 -6 0 0 1 2 -1 y = 0 0 0 -6 0 0 1 2 -1 y = 0 0 0 -6 0 0 1 2 -1 y = 0 0 0 -6 0 0 1 2 0 y = -6